2023
DOI: 10.1002/mgg3.2228
|View full text |Cite
|
Sign up to set email alerts
|

MRI characteristics due to gene mutations in a Chinese pedigree with Lafora disease

Abstract: Background and PurposeLafora disease (LD) is a very rare autosomal recessive disorder manifesting primarily as fatal, congenital, and neurodegenerative epilepsies. We aimed to describe the MRI characteristics due to gene mutations in a Chinese pedigree with LD.MethodsWhole‐exome sequencing, muscle biopsy, pedigree analysis, and MRI analysis were conducted. Five family members (two of whom were affected by LD) were whole‐genome sequenced. Longitudinal changes in brain MRI volumes were analyzed by Freesurfer.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Several studies have looked for imaging and electroretinogram (ERG) abnormalities that could either serve as biomarkers or, at the very least, shorten the duration of the diagnostic process for patients and their families. A case report from China identified a patient with LD who was found to have non-specific global brain atrophy on MRI at the time of diagnosis [48]. This finding differs from a 2006 cohort imaging study of patients with LD, which identified minimal MRI brain volume changes but significant MRS changes in frontal cortex and basal ganglia [49].…”
Section: Diagnostic and Phenotypic Advancesmentioning
confidence: 71%
“…Several studies have looked for imaging and electroretinogram (ERG) abnormalities that could either serve as biomarkers or, at the very least, shorten the duration of the diagnostic process for patients and their families. A case report from China identified a patient with LD who was found to have non-specific global brain atrophy on MRI at the time of diagnosis [48]. This finding differs from a 2006 cohort imaging study of patients with LD, which identified minimal MRI brain volume changes but significant MRS changes in frontal cortex and basal ganglia [49].…”
Section: Diagnostic and Phenotypic Advancesmentioning
confidence: 71%
“…When histological features are described, (i) they refer to skin biopsy [25] or (ii) authors do not specify the analyzed tissue [39]. A single study described the muscle biopsy of a LD patient harboring a homozygous EPM2A mutation [40]: histological analysis highlighted uneven muscle fiber dimensions, with most of the fibers showing considerable sarcoplasmic vacuolization; whilePAS staining identified the presence of PAS-positive polyglucosan aggregates.…”
Section: Discussionmentioning
confidence: 99%